POTENSI LIMBAH DAN KARAKTERISTIK PROSES PENGOMPOSAN TANDAN KOSONG KELAPA SAWIT YANG DITAMBAHKAN SLUDGE LIMBAH PABRIK MINYAK KELAPA SAWIT - L Syahwan, Firman (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Empty Fruit Bunches (EFB) and sludge are 2 (two) kinds of solid waste of palm oilplant that havenÃ¢â‚¬â„¢t been utilized optimally. Their potency are high enough, and both haveÃ‚Â different characteristic that positively influence each other if both utilized together. TheÃ‚Â research result showing that composting process of EFB added by sludge is optimallyÃ‚Â aerobic done with processing time about 13 weeks to produce mature compost. TheÃ‚Â addition of sludge is positively influence composting process of EFB that its compostÃ‚Â product has good quality.Key words : crude palm oil, empty fruit bunches, sludge, composting.